Pengaruh Leverage Dan Ukuran Perusahaan Terhadap Kebijakan Dividen Pada Perusahaan Sektor Transportasi Dan Logistik Yang Terdaftar Di Bursa Efek Indonesia Tahun 2020-2025 - Putri, Melati Dwi; Hiyah, Siti Asrorotul Ikah; Handayani, Annisa; Herdiyanti, Devi; Linawati, Linawati (Jurnal Portofolio : Jurnal Manajemen dan Bisnis, 2026)
This study aims to examine the effect of leverage and company size on dividend policy in transportation and logistics companies listed on the Indonesia Stock Exchange for the 2020–2024 period. The sample was selected using purposive sampling, resulting in 8 companies with a total of 40 panel data observations. Leverage is measured by the Debt to Equity Ratio, company size using Ln Total Assets, and dividend policy is proxied by the Dividend Payout Ratio. The analysis was conducted using multiple linear regression with the Common Effect Model (Pooled OLS) in EViews 10 software. The results show that neither leverage nor company size has a significant effect on dividend policy. The contribution of both variables to dividend distribution decisions is very small, so most variations in dividend policy are influenced by other factors.